Adherence to tuberculosis treatment among patients attending national tuberculosis elimination centre in tertiary care hospital, Bangalore - John, Julie K.; Parasuramalu , B. G. (International Journal Of Community Medicine And Public Health, 2023)
Background: Annually ten million cases of tuberculosis (TB) and 1.8 million mortalities are recorded. Adherence to TB treatment not only reduces death outcomes but prevents prolonged sickness, transmission to others and development of multi drug resistant TB. This study was aimed at determining the rate of treatment adherence and possible factors influencing adherence to TB treatment in the NTEP Centre at Rajarajeswari medical college and hospital, Bangalore. Methods: It was a cross sectional study design. A validated 8 item Morisky medication adherence scale was used to obtain data from respondents. Adherence to TB treatment was assessed. Chi square test was used to determine the variables that were associated with treatment adherence. Results: Out of 60 patients, majority i.e. 18 (30%) were in the age group 25-34 years, males were more compared to females. Majority i.e. 21 (35%) were studied up to post high school diploma, 31(51.67%) were unemployed, majority i.e. 48 (80.00%) were married, 42 (70.00%) were from nuclear family. Out of 60 patients, majority 54 (90.00%) were Hindus 24 (40.00%) were from lower middle class. Conclusions: The adherence rate for TB treatment in this study was 68.33%. There was no significant association between socio demographic variables, personal habits, health status, current TB status, type of TB, and common symptom with treatment adherence. An intensified health education on the adherence of TB treatment therefore recommended.